2008
DOI: 10.1002/cncr.23695
|View full text |Cite
|
Sign up to set email alerts
|

Agent Orange exposure, Vietnam War veterans, and the risk of prostate cancer

Abstract: BACKGROUND. It has been demonstrated that Agent Orange exposure increases the risk of developing several soft tissue malignancies. Federally funded studies, now nearly a decade old, indicated that there was only a weak association between exposure and the subsequent development of prostate cancer. Because Vietnam War veterans are now entering their 60s, the authors reexamined this association by measuring the relative risk of prostate cancer among a cohort of men who were stratified as either exposed or unexpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 23 publications
3
47
0
1
Order By: Relevance
“…Fatty fish, which contain a range of contaminants that are detrimental to health, are the main source of n23 PUFAs. It is possible that, in our study population, plasma n23 PUFAs are markers of dioxin contamination (35), for which there is only inconsistent evidence of an association with prostate cancer risk (36,37). Overall, fish intake has not been consistently linked to the risk of prostate cancer (38), but is associated with the likelihood of early detection (39).…”
Section: Discussionmentioning
confidence: 86%
“…Fatty fish, which contain a range of contaminants that are detrimental to health, are the main source of n23 PUFAs. It is possible that, in our study population, plasma n23 PUFAs are markers of dioxin contamination (35), for which there is only inconsistent evidence of an association with prostate cancer risk (36,37). Overall, fish intake has not been consistently linked to the risk of prostate cancer (38), but is associated with the likelihood of early detection (39).…”
Section: Discussionmentioning
confidence: 86%
“…Of the remaining 59 articles [1132,3874], 51 articles were included in the meta-analysis. We report results of the other eight articles without including them in the meta-analysis [16,40,41,51,52,58,73,74] because they did not provide enough information to do so. Two authors (F.I.…”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…Of these eight articles (Supplementary Table 1b), three reported on morality [40,52,73], four reported on incidence [16,51,58,74], and one reported on both [41], with an additional 1000 PCa deaths, 1344 incident cancers, and 225 451 cohort participants. One study reporting on current cigarette smoking (37 PCa deaths) [40], and another study reporting on ever smoking (12 deaths) [41] found no significant associations between smoking and PCa mortality.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Adverse effects associated with exposure to BPA have been reported in a wide range of vertebrate species from fish (4) to rodents (reviewed in 5) to primates (6) and humans (7Á10). These effects suggest but do not prove that BPA is implicated in a wide array of human health conditions, including heart disease (7,8), Type 2 diabetes (7), breast cancer (11), prostate cancer (12), infertility (13), and neurodevelopmental disorders, including attention deficit hyperactivity disorder (14).…”
Section: Introductionmentioning
confidence: 98%